Links between medical interns’ perceived stress, workaholism and personality: a cross-sectional study - Mathilde Chaillet; Joana Pissarra; Lionel Moulis; François-Xavier Lesage; Cédric Julien (BMC Medical Education)
Abstract Background Medical interns’ work conditions and individual features make them vulnerable to stress and deterioration in their physical and mental health. Moreover, these factors are associated with a pathological relationship with work, workaholism. Few studies have focused on this population, and its exposure to psychosocial risks and related consequences. We evaluated the perceived stress of medical interns with regard to their personality and the risk of workaholism. Methods This cross-sectional observational study was carried out using a self-administered questionnaire, anonymously, assessing perceived stress (PSS-10), personality (BFI-10) and the risk of workaholism (DUWAS-10). Results 358 medical interns were included in the study. We found that perceived stress was positively associated with neuroticism and the risk of workaholism and, on the other hand, negatively associated with a conscientious personality. The risk of workaholism increased with perceived stress, number of weekly work hours and conscientiousness trait. Having time for leisure was associated with a reduction in both perceived stress and the risk of workaholism. Conclusions Among medical interns, our results further supported that perceived stress, risk of workaholism and personality are intertwined. A better understanding of these mechanisms will contribute to the identification of the most vulnerable interns, to the improvement of targeted screening and prevention tools of psychosocial risks, usable during occupational medicine consultations. Clinical trial number Not applicable.